ANALISIS JOB PERFORMANCE PEGAWAI HONORER ADMINISTRASI DENGAN KOMPETENSI DAN JOB CHARACTERISTICS DALAM MENDUKUNG UNIVERSITAS PENDIDIKAN INDONESIA MENCAPAI LEADING AND OUTSTANDING - Masharyono .; Syamsul Hadi Senen (STIE Pelita Nusantara Semarang, 2015)
Collage are required to prepare in order to be college ready to compete with other universities. Factors which later played a role in achieving this is the quality of human resources. One of the quality of human resources is to have a good performance. Therefore, it needs good human resource management. Human existence as human resources is very important in the organization because of human resources to support organizations exist through the work, talent, creativity, encouragement and role as real as can be seen in every organization. Without the human element in an organization, the organization may not be able to move towards the desired and as well as the University of Indonesia. Where success in achieving organizational goals is largely determined by the performance of its employee. One effort to improve performance is to improve the competence of employees and job characteristics of the employees themselves who will support in completing the works